Characterisation of Asphaltenes Extracted from an Indonesian Oil Sand Using NMR, DEPT and MALDI-TOF. (August 2015) - Zheng, Ce; Zhu, Mingming; Zhang, Dongke
Abstract: This paper reports the findings of a preliminary study into the molecular structure and properties of asphaltenes extracted from an Indonesian oil sand, Buton Oil Sand. The molecular structural parameters of the asphaltenes were determined using liquid 13 C NMR spectrum in combination with DEPT. The molecular weight distribution of the asphaltenes was measured using MALDI-TOF mass spectrometer. The results indicated that the representative molecular structure of the asphaltenes from Buton Oil Sand predominately contained only one PAH core of 6 rings with an average molecular weight around 800 Da. The results also showed that the use of 13 C NMR spectrum/DEPT provided a powerful tool and useful method for characterising and predicting the molecular structures of asphaltenes.